Genome analysis of Salmonella enterica serovar enteritidis strains isolated from poultry and humans in Burkina Faso - Kagambèga, A.; Ramadan, H.; Dione, Michel M.; Bouda, S.C.; Hiott, L.M.; McMillan, E.A.; Sharma, P.; Gupta, S.K.; Barro, N.; Jackson, C.R.; Frye, J.G. (American Society for Microbiology, 2024)
Whole-genome sequencing (WGS) was used to characterize four Salmonella enterica Enteritidis isolates from poultry (n=2) and human (n=2) from Ouagadougou, Burkina Faso. Antimicrobial resistance genes, chromosomal mutations, and mobile genetic elements were identified by analysis of WGS data using sequence homology.